Prefiguring sustainable futures? Young people's strategies to deal with conflicts about climate-friendly food choices and implications for transformative learning. Issue 8 (1st August 2022) - Ojala, Maria
Abstract: Transformative learning is important for handling climate change. How to include this kind of learning in formal education is, however, still debated. This article takes a bottom-up approach by learning from young people who make climate-friendly food choices to a high degree. Interviews were performed with Swedish adolescents. By focusing on conflicts and coping the aim was to explore if there are elements of prefigurative practice (e.g. to actualize ideals about the future in the here and now) in the young people's everyday engagement and to discuss how to utilize these to promote transformative learning. The young people experienced, for example, interpersonal, intrapersonal, and structural/practical conflicts. They coped in two overarching ways: strategies to support climate-friendly choices despite conflicts and strategies to deal with less good choices. It is argued that by critically discussing conflicts and different ways of dealing with them transformative learning can be promoted.